Earning Your Way into General Education: Perceptions about Autism Influence Classroom Placement - Emily Frake; Michelle Dean; Linh N. Huynh; Suzannah Iadarola; Connie Kasari (MDPI AG, 2023)
The language used by teachers, school staff, and parents to talk about autistic students can send either positive or negative messages to other school staff, parents, and all students-with or without autism-about autistic students. Ultimately, these messages also extend to autistic people. Using qualitative focus group methods, we talked to parents, teachers, administrators, and other school staff to better understand how people speak about the inclusion of autistic students in general education classrooms in public schools. Overall, we found that many of our participants thought (1) autistic students need to earn their way into general education classrooms, unlike their peers without disabilities, (2) segregating students with disabilities away from their peers without disabilities is acceptable, and sometimes preferable, in school settings, and (3) there is power in inclusive education opportunities for students with and without disabilities in school settings. The findings from this study suggest that inclusive opportunities for autistic students were largely driven by stakeholder mindsets. These results should encourage school staff to think about and reflect on how they talk about autistic students in inclusive settings with the ultimate goal of creating more welcoming inclusive environments for autistic students.